STRATEGI OPTIMALISASI LAYANAN E-RESOURCES PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA DI MASA PANDEMI COVID-19 - Siti Haja, Safira; Fauziah, Kiki (BACA: Jurnal Dokumentasi dan Informasi, 2022)
This study discusses the strategy for optimizing e-Resources services for the National Library of Indonesia (Perpusnas) during the COVID-19 pandemic. During the COVID-19 pandemic, Perpusnas stated that all online library services had increased three times. Perpusnas provides free open access services to local and international publications through the e-Resources portal. However, during 2020, statistical data shows a decrease in visitors to the e-Resources portal. The decrease in visitors to the National Library of Indonesia's e-Resources services is not proportional to the increase in all online services from the National Library of Indonesia. Therefore, the research problem is how the National Library of Indonesia's strategy in optimizing e-Resources services during the COVID-19 pandemic. The purpose of this research is to find an effective strategy for optimizing e-Resources services during the COVID-19 pandemic. This research uses a qualitative approach with a case study method, where data collection was carried out by online interviews with the National Library librarians and online observations of e-Resources digital collection services. The results show that the National Library of Indonesia's strategies in optimizing the use of e-Resources includes online user guidance, collaboration with universities, promotion on social media, and the Ask a Librarian service.